Ultranationalism in German-Japanese relations : 1930 - 45 ; from Wenneker to Sasakawa - Chapman, John William 1923-2008 (Global Oriental, 2011)
This study focusing on the ultranationalist regimes in Germany and Japan during the 1930s and 1940s examines in biographical format the roles played by individuals significantly involved in the drive for global hegemony